Tantangan & Strategi dalam Optimalisasi Ekspor Produk Fashion dan Perhiasan Dengan Pendekatan Digital - Irgi Putri Olivia; Ni Made Ida Pratiwi (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
Technological developments are closely related to the trading system, especially export activities. Developing technology with various existing applications is the right choice because it makes international trade increasingly have a very broad market coverage. Export activities for an MSME apart from needing media that makes the MSME more known to more people and more widespread, it also needs a place as a forum for training and information about digitalization. PT. Lacorre Loka Maya is a digitally oriented learning institution providing Digital Export training for spices and fashion. This training aims to produce young exporters who can develop local products in the spice and fashion sectors so they are ready to enter the global market.